IMPLEMENTASI KOMPETENSI SOSIAL OLEH GURU PENDIDIKAN AGAMA KATOLIK UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Situmorang, Vinsensius M. Junior; Pasaribu, Astina Vebriani (STP St. Bonaventura Medan, 2023)
This research examines the significance of Catholic Religious Education teachers' social abilities in influencing students' motivation to learn. The social skills of teachers encompass objective attitudes and behaviors, adaptability to the environment, effective communication skills, as well as empathy and politeness in communication. A qualitative research method was employed, involving data collection through interviews, observations, and analysis conducted at Budi Murni 4 Private Middle School in Medan. The study participants consisted of 10 individuals, including Catholic Religious Education Teachers, Peer Teachers, and students who were selected using purposive sampling and snowball sampling techniques. The findings indicate that Catholic Religious Education teachers with good social skills can enhance students' interest in learning. Teachers who exhibit an objective attitude, possess adaptability to the environment, and demonstrate effective communication skills can assist students in the learning process. Therefore, it is crucial for Catholic Religious Education teachers to develop their social skills in order to enhance students' learning motivation. Key words: social competence ,interest to learn